Quantifying Geobacter sulfurreducens growth: A mathematical model based on acetate concentration as an oxidizing substrate - Virgínia Villa-Cruz; Sumaya Jaimes-Reátegui; Juana E. Alba-Cuevas; Lily Xochilt Zelaya-Molina; Rider Jaimes-Reátegui; Alexander N. Pisarchik (Mathematical Biosciences and Engineering, 2024)
We developed a mathematical model to simulate dynamics associated with the proliferation of Geobacter and ultimately optimize cellular operation by analyzing the interaction of its components. The model comprises two segments: an initial part comprising a logistic form and a subsequent segment that incorporates acetate oxidation as a saturation term for the microbial nutrient medium. Given that four parameters can be obtained by minimizing the square root of the mean square error between experimental Geobacter growth and the mathematical model, the model underscores the importance of incorporating nonlinear terms. The determined parameter values closely align with experimental data, providing insights into the mechanisms that govern Geobacter proliferation. Furthermore, the model has been transformed into a scaleless equation with only two parameters to simplify the exploration of qualitative properties. This allowed us to conduct stability analysis of the fixed point and construct a co-dimension two bifurcation diagram.